2020
DOI: 10.1159/000509518
|View full text |Cite
|
Sign up to set email alerts
|

Career and Financial Situation of Patients Diagnosed with Soft Tissue Sarcomas

Abstract: Background: After receiving a cancer diagnosis patients face many challenges. The association between career situation and financial problems caused by cancer has a substantial impact on quality of life (QoL) among cancer patients. Indeed, the QoL such as physical and mental health of cancer patients is lower when the risk of psychological disorders or distress increases, and chances for cancer cure are reduced. Progress in therapeutic intervention allows many cancer patients a social reintegration into their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Patients with sarcoma show the lowest return to work rates [34] and are considered to have a higher risk of not returning to work [35,36]. A study by Laros et al [37] showed that sarcoma patients in Germany had an average unemployment rate of 8.8 months and that for 67% of the sarcoma patients, the work situation changed after the unemployment phase. Patients in Germany are allowed up to 72 weeks of sick leave before returning to work or applying for a pension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with sarcoma show the lowest return to work rates [34] and are considered to have a higher risk of not returning to work [35,36]. A study by Laros et al [37] showed that sarcoma patients in Germany had an average unemployment rate of 8.8 months and that for 67% of the sarcoma patients, the work situation changed after the unemployment phase. Patients in Germany are allowed up to 72 weeks of sick leave before returning to work or applying for a pension.…”
Section: Discussionmentioning
confidence: 99%
“…The average full disability pension, which applies if you are not able to work more than 3 h a day, was €850 in 2019 [41], indicating a severe income decline for patients who were fully working before their disease. Laros et al [37] found an income loss of 62% on average for sarcoma patients in Germany who applied for a pension or partial or total unemployment benefits. The effect of this income decline is expressed in a statistically significantly increased chance of financial toxicity for patients receiving disability pension in our analysis, where having a disability pass was associated with higher odds of reporting financial toxicity.…”
Section: Discussionmentioning
confidence: 99%